2017
DOI: 10.9734/ijbcrr/2017/34077
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Protocol for Best Blending Ratio of Papaya cv. Red Lady and Guava cv. Allahabad Safeda Fruit Pulp for Preparation of Fruit Bar

Abstract: The papaya and guava pulps were blended in the ratios of 100:0, 80:20, 60:40, 50:50 and 40: 60 in preparation of fruit bar and physicochemical analysis and sensory attributes were evaluated at zero (initial), 30 and 60 days of storage. Among the different blending ratios, fruit bar prepared with 60% papaya pulp + 40% guava pulp (T 3 ) was selected as best ratio (combination) as the treatment had maximum score for sensory attributes i.e., overall acceptability (8.75). The microbial load recorded in the same tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Jam stored at ambient temperature exhibited more prominent decrease in the moisture content as compared to one stored at low temperature. There are reports that storage of jam can decrease the moisture content [7,12] . Chavan and Shaik (2015) [7] reported that moisture loss is more rapid under ambient condition than under refrigerated condition.…”
Section: Moisture Content Of Jammentioning
confidence: 99%
See 4 more Smart Citations
“…Jam stored at ambient temperature exhibited more prominent decrease in the moisture content as compared to one stored at low temperature. There are reports that storage of jam can decrease the moisture content [7,12] . Chavan and Shaik (2015) [7] reported that moisture loss is more rapid under ambient condition than under refrigerated condition.…”
Section: Moisture Content Of Jammentioning
confidence: 99%
“…However, fresh fruits are liable to deteriorate owing to high ambient temperature and humidity, pest and disease infestation, improper handling and poor storage facilities [22] . One of the most handy, attractive and effective method of reducing loss is to process and preserve fruits in durable edible forms [12] . Converting fruit to preserves, jams, sauces, pickles and chutneys is an age-old Indian tradition.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations